Evaluasi Pelatihan Jarak Jauh Dimasa Pandemi - Akhmadi, Agus (Inovasi: Jurnal Diklat Keagamaan, 2020)
This study is aimed at evaluating distance training. Evaluation uses context, input, process and product theory. This research is a survey with a quantitative descriptive approach. Research respondents were 35 teachers of Guidance and Counseling at Madrasah Aliyah East Java. The research instrument is a questionnaire uploaded on google form. Data analysis using descriptive statistics. The results showed that distance training was carried out in the medium category. Judging from the context and input from the participants, it shows a moderate category, so it is necessary to improve infrastructure and support from participants. In the process and product components, it shows a medium category with a high tendency.